Metoprolol Impairs β1-Adrenergic Receptor-Mediated Vasodilation in Rat Cerebral Arteries: Implications for β-Blocker Therapy - Moore, Christopher L. (J Pharmacol Exp Ther, 2021)
The practice of prescribing β-blockers to lower blood pressure and mitigate perioperative cardiovascular events has been questioned because of reports of an increased risk of stroke. The benefit of β-blocker therapy primarily relies on preventing activation of cardiac β1-adrenergic receptors (ARs). However, we reported that β1ARs also mediate vasodilator responses of rat cerebral arteries (CAs), implying that β-blockers may impair cerebral blood flow under some conditions. Here, we defined the impact of metoprolol (MET), a widely prescribed β1AR-selective antagonist, on adrenergic-elicited diameter responses of rat CAs ex vivo and in vivo. MET (1–10 µmol/l) prevented β1AR-mediated increases in diameter elicited by dobutamine in cannulated rat CAs. The β1AR-mediated dilation elicited by the endogenous adrenergic agonist norepinephrine (NE) was reversed to a sustained constriction by MET. Acute oral administration of MET (30 mg/kg) to rats in doses that attenuated resting heart rate and dobutamine-induced tachycardia also blunted β1AR-mediated dilation of CAs. In the same animals, NE-induced dilation of CAs was reversed to sustained constriction. Administration of MET for 2 weeks in drinking water (2 mg/ml) or subcutaneously (15 mg/kg per day) also resulted in NE-induced constriction of CAs in vivo. Thus, doses of MET that protect the heart from adrenergic stimulation also prevent β1AR-mediated dilation of CAs and favor anomalous adrenergic constriction. Our findings raise the possibility that the increased risk of ischemic stroke in patients on β-blockers relates in part to adrenergic dysregulation of cerebrovascular tone. SIGNIFICANCE STATEMENT: β-Blocker therapy using second-generation, cardioselective β-blockers is associated with an increased risk of stroke, but the responsible mechanisms are unclear. Here, we report that either acute or chronic systemic administration of a cardioselective β-blocker, metoprolol, mitigates adrenergic stimulation of the heart as an intended beneficial action. However, metoprolol concomitantly eliminates vasodilator responses to adrenergic stimuli of rat cerebral arteries in vivo as a potential cause of dysregulated cerebral blood flow predisposing to ischemic stroke.